NEUROBEHAVIORAL EVALUATION OF NARDOSTACHYS JATAMANSI IN REVERSING METOCLOPRAMIDE-INDUCED CATALEPSY IN RATS. - M A ALEEM; IBRAHIM M (International Journal of Pharma and Bio Sciences, 2016)
Oxidative stress has been evidenced to play a vital role in its causation of catalepsy a neurodegenerative disorder. The current study was carried out on Hydroalcoholic rhizomes extracts HAE1 (75:25) & HAE2 (50:50) of Nardostachys Jatamansi for its potential in reversing metoclopramide –induced catalepsy in rats. Catalepsy can be induced by metoclopramide (20 mg/kg i.p) in adult Wister rats of either sex. Treatment with hydroalcoholic extract shows a reduction in the cataleptic scores when compared to metoclopramide (toxicant) treated group. There were no signs of toxicity in the animals observed and no significant change in body weight either before or after the treatment. The hydroalcoholic extract HAE1 (500mg/kg) of N. Jatamansi shown a maximum reduction in catalepsy than HAE2 (500mg/kg). The biochemical parameters like reduced glutathione (GSH), thiobarbituric acid reactive substances (TBARS) and glutathione dependent enzymes catalase and superoxide dismutase (SOD) is restored to a normal level in drug treated animals when campare to the animals of toxicant group. Extracts of N. Jatamansi upturned the biochemical and behavioral parameters of metoclopramide–induced catalepsy in rats. The contributing factors in reducing catalepsy are due to anti-oxidant & biogenic amines enhancing activity of N. Jatamansi.